Pengaruh Strategi Bauran Pemasaran Digital Terhadap Kinerja Pemasaran melalui Manajemen Hubungan Pelanggan di Objek Wisata Pantai Randusanga Indah Brebes - Riyadi Riyadi; Syariefful Ikhwan; Azizah Indriyani; Andi Yulianto (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of digital marketing mix strategy on marketing performance through customer relationship management at Randusanga Indah Brebes Beach tourist attraction. Using quantitative and qualitative approaches, this research sample involved 203 respondents who were beach visitors who were taken using purposive sampling techniques. Data analysis was conducted using the Structural Equation Modeling (SEM) model with the AMOS program. The results showed that the digital marketing mix strategy had a significant effect on customer relationship management with a CR value of 11.252 (CR ≥1.96) and a probability value ≤ 0.05. However, the digital marketing mix strategy has no significant effect on marketing performance with a CR value of -,434 (CR ≥1.96) and a probability value of 0.664 (p ≤ 0.05). Similarly, customer relationship management also has no significant effect on marketing performance with a value of CR 1,261 (CR ≥1.96) and a probability value of 0.207 (p ≤ 0.05).